Domain Orientation and Grain Coarsening in Cylinder-Forming Poly(styrene-b-methyl methacrylate) Films - Ji, Shengxiang; Liu, Chi-Chun; Liao, Wen; Fenske, Alyssa L; Craig, Gordon S. W; Nealey, Paul F (Macromolecules, 2011)
The domain orientation and grain sizes in cylinder-forming poly(styrene-b-methyl methacrylate) (PS-b-PMMA) films were systematically investigated as a function of film thickness (32–640 nm), annealing temperature (190–230 °C), and wetting behavior of PS-b-PMMA on substrates. The domain orientation at the film surface depended on film thickness as well as both the polymer–substrate and polymer−free surface boundary conditions. In thin films (thickness L < 3L 0, where L 0 is the domain period of the block copolymer), the polymer–substrate boundary condition dominated and determined the domain orientation of the block copolymer. At intermediate thicknesses (3L 0 < L < 6L 0) the interplay of both boundary conditions usually resulted in the formation of a mixed structure. In films with L > 6L 0, the two boundary conditions decoupled, and the polymer-free surface interaction determined the domain orientation of cylinders near the film surface regardless of the chemistry of the underlying substrate. The orientational correlation length (ξ) of grains of perpendicular cylinders at the surface increased with the increase of annealing temperature for films of equal L. The grains coarsened at 210 and 230 °C, and the corresponding ξ’s scaled with annealing time (t) according to a power law, ξ ∼ t ϕ, with ϕ = 0.28 ± 0.01. ξ’s also increased linearly with L. In films annealed at 190 °C, the ξ’s were nearly constant with increasing L. The technical significance of this work is that the surface domain pattern with a large ξ can be achieved on the surface of thick films and the surface pattern can be successfully replicated by molecular transfer printing (MTP) to create a chemical pattern with the same ξ without the use of lithographic tools.